2018
DOI: 10.1136/bmjopen-2017-020884
|View full text |Cite
|
Sign up to set email alerts
|

Emotional reserve and prolonged post-concussive symptoms and disability: a Swedish prospective 1-year mild traumatic brain injury cohort study

Abstract: ObjectiveProlonged post-concussive symptoms (PCS) affect a significant minority of patients withmild traumatic brain injury (mTBI). The aetiology is multifactorial depending on preinjury as well as peri-injury and postinjury factors. In this study, we examine outcome from an emotional reserve perspective.DesignProspective cohort study.SettingPatients were recruited from three emergency departments in major university hospitals in Stockholm, Sweden. Follow-up data were collected in an outpatient setting at one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 64 publications
(57 reference statements)
4
18
0
Order By: Relevance
“…Personality characteristics were also related to persistent symptoms. Not surprisingly, neuroticism, a personality trait linked to an increased tendency of experiencing negative emotions and distress, was associated with PCSs, in line with other studies of patients with MTBI 37,43,44 and people without MTBI. 45 Further, low resilience was a risk factor for PCSs, similar to previous studies.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Personality characteristics were also related to persistent symptoms. Not surprisingly, neuroticism, a personality trait linked to an increased tendency of experiencing negative emotions and distress, was associated with PCSs, in line with other studies of patients with MTBI 37,43,44 and people without MTBI. 45 Further, low resilience was a risk factor for PCSs, similar to previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…45 Further, low resilience was a risk factor for PCSs, similar to previous studies. 37,[46][47][48][49] Low resilience has previously been found to be associated with high neuroticism, 31 and these factors also were correlated in the present study. A person's resilience is considered to be more modifiable than personality traits, 50,51 possibly making it a target for interventions after MTBI.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Furthermore, depression and anxiety might be risk factors for initially developing PCS. 71,72 Yet, studies on rodents have found evidence of causality, in which induced mTBI disrupts limbic system function, subsequently leading to long lasting depressive, fearful and anxious behavior. [73][74][75] Whatever the case, the neuropsychological nature of PCS makes providing psychosocial coping strategies a viable part of the multidisciplinary approach, and some reviews have supported the use of cognitive behavioral therapy in improving psychosocial outcomes 76 ; however, more research is needed.…”
Section: Best Research Evidencementioning
confidence: 99%